Paediatric pain assessment and management survey within the Rahima Moosa Mother and Child Hospital - Mabaso, Lindiwe N M (My University, 2021)
Background: Painful experiences are prevalent within the paediatric inpatient population. Immaturity and cognitive impairment may preclude competent expression of such experiences, and the need for analgesia. Methods of pain assessment and guidelines for treatment in the paediatric population are well establishedbutare not widely used around the world. Limited data suggests that the situation is similar in South Africa. The study aims to review the assessment and management of pain in South African medical paediatric inpatients. Objectives: The primary objective was to determine the proportion of children who receive analgesia where indicated. The secondary objectives were to determine thei ncidence of pain at presentation, the prevalence of pain amongst admitted patients, if pain evaluations are done and if pain is treated, and the adequacy of such treatment. Methods: The study was a prospective cross-sectional survey of medical paediatric inpatients at Rahima Moosa Mother and Child Hospital. The tool used for data collection was designed uniquely for this study, with sections for demographic data, patient or caregiver interview and review of the patient chart. Pain assessments were done using therevised Faces, Legs, Activity, Cry and Consolability score and the Neonatal/Infant Pain Scale. The analysis consists of descriptive statistics of epidemiological data and comparative statistics using grouped variables with significance level set at p < 0.05. Results: The sample consisted of 74 participants aged three days to four years old and 58% were male. The incidence of pain at admission was found to be 73% (53 participants). Eight percent (six participants) of the study sample had pain evaluation at admission, and only one patient was evaluated for pain within the 24 hours preceding study participation. Of the 74 patients reviewed, seven (9.5%) received appropriate analgesia. Paracetamol was given to 23 (31%) patients, either for pyrexia, or the indication was not documented. More than half of the study sample -44 (59.5%) -received no analgesia . The presence of pain, both by caregiver report (p =1) and by pain score (p = 0.096), was not associated with the administration of analgesia. Conclusion: Pain in the paediatric population at RMMCH is common, it is seldom assessed, and validated pain scores are rarely used. The result is pain management which is inadequate in all three domains of assessment, treatment and re-evaluation.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine (Paediatrics), 2021